2022
DOI: 10.3390/molecules27196260
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality of Burkina Faso Soybeans Based on Fatty Acid Composition and Pesticide Residue Contamination

Abstract: Soybean is widely used in the food industry because of its high fatty acid and protein content. However, the increased use of pesticides to control pests during cultivation, in addition to being a public health concern, may influence the nutritional quality of soybeans. This study aimed to assess the nutritional quality of soybeans with respect to fatty acid profile and pesticide residue contamination. The levels of fatty acids and pesticides in soybean varieties G196 and G197 were determined by gas chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…This indicated that melatonin could significantly promote the accumulation of these secondary metabolites in soybean sprouts, especially isoflavones, which are beneficial to human health [ 55 , 56 ]. Moreover, the fatty acid composition has been considered a biomarker to determine the response of organisms to pesticides [ 57 , 58 ]. The decrease in the unsaturated fatty acid content (C 18:1 , C 18:2 , and C 18:3 ) in soybean sprouts caused by pesticides could be significantly restored by exogenous melatonin ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that melatonin could significantly promote the accumulation of these secondary metabolites in soybean sprouts, especially isoflavones, which are beneficial to human health [ 55 , 56 ]. Moreover, the fatty acid composition has been considered a biomarker to determine the response of organisms to pesticides [ 57 , 58 ]. The decrease in the unsaturated fatty acid content (C 18:1 , C 18:2 , and C 18:3 ) in soybean sprouts caused by pesticides could be significantly restored by exogenous melatonin ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Together with medicinal plants, this presented Special Issue is presented to study and assess the nutritional quality of soybeans concerning fatty acid profile and pesticide residue contamination [14]. Assessing the quality of Burkina Faso soybeans, based on fatty acid composition and pesticide residue contamination, showed a significant variation in the quantitative and qualitative fatty acid composition of the two soybean varieties.…”
mentioning
confidence: 99%
“…Assessing the quality of Burkina Faso soybeans, based on fatty acid composition and pesticide residue contamination, showed a significant variation in the quantitative and qualitative fatty acid composition of the two soybean varieties. The profile of fatty acids and the content of pesticide residues were used as important determinants for soybean utilization in human nutrition [14].…”
mentioning
confidence: 99%
“…The use of natural and mineral formulations as biostimulants for plant growth or as new strategies of pest control (Glenn andPuterka 2010, De Smedt et al 2015) has gained interest in agriculture, with the specific purpose of mitigating plant water stress and improving the water-use efficiency (Cirillo et al 2021) and reducing the risks for human health due to pesticide utilization. This issue is of particular interest since the high concentration of chemicals present in the environment poses serious health risks, not only for the environment itself but also for human health (Mahmood et al 2016, Rather et al 2017, Ouédraogo et al 2022.…”
mentioning
confidence: 99%